THE CONDENSATION OF FURFUROL IN AN ALKALINE MEDIUM (Scientific journal of the Fergana State University, 2023)
In this paper, studies of the condensation of furfurals with furfurals and acetone in an alkaline medium are presented, as well as their conversion by UV, IR, NMR spectroscopic and chromatographic methods. It has been established that with a decrease in temperature within the range of minus 150°C, the conversion of furfural by the Canizzaro reaction swells, and in order to obtain the maximum content of difurfurylideneacetone - DIFA in the preparation of the DIFA monomer, the temperature of the reaction mass must be raised from + 200 ° C to 85 ± 50 ° C, an increase in the content of DIFA to 96 ± 2%.